The Effect of Work Motivation And Work Environment On Employee Performance With Work Satisfaction As A Mediation Variable At Pt. Suryabumi Agrolanggeng, Penukal Abab Lematang Ilir Regency (Pali - Anggini, Lia; Asiati, Diah Isnaini; Yamaly, Fadhil (International Journal of Business, Management and Economics, 2025)
This study aims to determine the effect of work motivation and work environment on employee performance with job satisfaction as a mediating variable at PT. Suryabumi Agrolanggeng, Penukal Abab Lematang Ilir Regency (PALI). This type of research is Associative. The variables used by researchers are work motivation variables, work environment, job satisfaction and employee performance. The sample in this study were 120 employees of PT. Suryabumi Agrolanggeng, Penukal Abab Lematang Ilir Regency (PALI) who were selected using Cluster Random Sampling. The data used in this study were primary data with a questionnaire data collection method. The data analysis technique used was Structural Modeling Equation (SEM) with the Lisrel Program Application. The results of this study indicate that: (1) Work motivation has a positive and significant effect on job satisfaction (2) Work environment has a positive and significant effect on job satisfaction (3) Work motivation has a positive and significant effect on employee performance (4) Work environment has a positive and significant effect on employee performance (5) Job satisfaction has a positive and significant effect on employee performance (6) Job satisfaction strengthens the influence of work motivation on employee performance (7) Job satisfaction strengthens the influence of the work environment on employee performance